Meningkatkan Keterampilan Teknik Passing dalam Permainan Sepak Bola melalui Pendekatan Tutor Teman Sebaya - Halimi, Alpin; Safari, Indra; Supriyadi, Tedi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to improve basic passing technical skills in learning football. This research method uses a Classroom Action Research (PTK) design. The subjects in the study were 20 class V students consisting of 10 boys and ten girls at SDN Sukamaju Rancaekek, Bandung Regency. The research results in cycle I obtained a completeness score of 40%, or as many as eight people had completed it. In cycle II, there was a completeness score of 70%, or as many as 14 people had completed it, and in cycle III, it was 95%, or 19 people had achieved the completion score. The conclusion is that peer tutoring can improve basic passing technical skills in fifth-grade students at SDN Sukamaju. Keywords: Peer tutoring, soccer games, soccer passing techniques